Analisis Buku Ajar MI Berstandar ACTFL - Iffat Maimunah; Moh Ainin; Muassomah Muassomah; Anwar Sanusi (Al-Fusha : Arabic Language Education Journal, 2022)
This research reports on the analysis of Arabic textbooks for elementary schools that have been published by the Ministry of Religion of the Republic of Indonesia based on American Council on the Teaching of Foreign Languages (ACTFL) guidelines. This research examined the competencies to be achieved from the practice of using textbooks in teaching Arabic based on the instructional objectives and concept maps included in the textbooks. The results of the study showed that the teaching materials had contained in the Arabic language textbooks for elementary school 1st, 2nd and 3th grade and had reflected ACTFL standards at a low novice level. These textbooks apart from being an authentic learning resource and promoting innovative learning can also be put into practice by teachers with formulated instructional ideas and strategies. The study findings reflect pedagogical discussions about teaching Arabic as a foreign language and allow teachers to build their creativity to practice contextual and transformative learning based on the standards formulated in textbooks.